The Influence of Mental Workload and Job Stress on Employee Performance (Study Case: PT. Sumber Alfaria Trijaya, Tbk) - Topik Nurfazar; Muhamad Sayuti; Hilda Tri Yulianti; Afif Hakim (JTI: Jurnal Teknik Industri, 2025)
This study investigates the impact of mental workload and work stress on employee performance in a retail setting, specifically at PT Sumber Alfaria Trijaya, Tbk. A quantitative approach was employed, utilizing questionnaires distributed to employees. The collected data were analyzed using validity and reliability tests, as well as multiple linear regression analysis. The findings indicate that mental workload significantly influences employee performance (p = 0.020), whereas work stress does not have a significant effect (p = 0.962). However, when examined simultaneously, both variables have a significant combined impact on performance (F = 10.216, p < 0.000). These results highlight the importance of managing mental workload to enhance employee productivity while ensuring that work stress is controlled to prevent adverse effects on performance. To optimize workforce efficiency, organizations should implement strategies for workload distribution and structured stress management programs. This study provides valuable insights for companies in the retail sector, emphasizing the need for balanced work demands and employee well-being to maintain high performance levels.Keywords: Mental Workload, Work Stress, Employee Performance, Retail Industry, Work Environment